Settlement of Land Procurement Disputes at the State Administrative Court - Sugiarto, Yuni; Mustomi, Otom (Budapest International Research and Critics University, 2021)
The purpose of this study is to analyze the legal protection for citizens over land acquisition disputes in determining the location of development for the public interest at the State Administrative Court. This research paper is included in the category of normative legal research. Data analysis in this type of normative legal research will use qualitative descriptive techniques. The results of this study provide an understanding of state-owned land disputes through the state administrative court. This study concludes that the implementation of the provisions of the Supreme Court Regulation Number 2 of 2016 concerning Guidelines for Proceeding in Disputes on Determining Development Locations for the Public Interest at the State Administrative Court is not effective in providing legal protection for the rights of citizens who are disadvantaged from the determination of development locations for the public interest By the Governor.